2022
DOI: 10.1186/s12890-021-01816-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive risk assessment for hospital-acquired pneumonia: sociodemographic, clinical, and hospital environmental factors associated with the incidence of hospital-acquired pneumonia

Abstract: Background Social and hospital environmental factors that may be associated with hospital-acquired pneumonia (HAP) have not been evaluated. Comprehensive risk assessment for the incidence of HAP including sociodemographic, clinical, and hospital environmental factors was conducted using national health insurance claims data. Methods This is a population-based retrospective cohort study of adult patients who were hospitalized for more than 3 days fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
10
0
1
Order By: Relevance
“… 21 , 22 Comorbidities, extremes of age, admitting service, and hospital type have also been found to be associated with development of HAIs. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“… 21 , 22 Comorbidities, extremes of age, admitting service, and hospital type have also been found to be associated with development of HAIs. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…It was found that the fatality rate of the Omicron variant of COVID-19 is low compared to other variants [ 28 ]. However, the mortality rate of nosocomial infection is influenced by various aspects, such as the general condition, comorbidities, immune status, and severity of diagnosis in patients [ 29 ]. In a study of Omicron nosocomial COVID-19, patients in the head and neck surgery ward had a mortality rate of zero [ 14 ], and another study found a mortality rate of 1.1% for rehabilitation medicine ward patients, healthcare workers, and caregivers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia masih menjadi permasalahan kesehatan di intensive care unit (ICU), terutama tipe hospital acquired pneumonia (HAP) dan ventilator associated pneumonia (VAP), yang seringkali menyebabkan acute respiratory distress syndrome (ARDS) yang meningkatkan mortalitas pada pasien. 1,2 Center for Disease Control and Prevention (CDC) melaporkan di Amerika Serikat, tahun 2022, terdapat 14,4% kematian akibat pneumonia dari 100.000 orang. 3 Indonesia sendiri melalui Riset Kesehatan Dasar (RISKESDAS) tahun 2018, mendapatkan prevalensi pneumonia sebesar 4%.…”
Section: Pendahuluanunclassified